Ionic Conducting and Surface Active Binder of Poly (ethylene oxide)-block-poly(acrylonitrile) for High Power Lithium-ion Battery. (1st April 2016) - Tsao, Chih-Hao; Hsu, Chun-Han; Kuo, Ping-Lin
Graphical abstract: Highlights: PEO-b-PAN binder conducts Li + inside and acts as a dispersant to LiFePO4 cathode. PEO-b-PAN binder shows low polarization and less interfacial resistance. The PEO-b-PAN binder delivers extraordinary capacities of 101 mAh g −1 at 10C-rate. Abstract: In this work, poly(ethylene oxide)-block-poly(acrylonitrile) (PEO-b-PAN) copolymer is used as a binder for LiFePO4 cathodes, where PEO-b-PAN not only conducts Li + inside the cathode but also acts as a dispersant to disperse LiFePO4 . This binder significantly increases the capacity under high discharge rate and overcome the limitation of LiFePO4 for high power density application. By XPS analysis, the incorporation of the PEO-b-PAN binder to the active materials of the LiFePO4 cathodes can be clearly observed from the binding energy of the nitrogen atom of the PEO-b-PAN. Due to the surface active properties of the PEO and PAN, PEO-b-PAN obviously increases the effective contact area and reduces electronical resistance. In addition to the surface active properties, this binder provides Li + pathway; thus, it features low polarization, less interfacial resistance and good activity for electrochemical reaction. Consequently, these properties enable the PEO-b-PAN binder to have a higher discharge plateau potential at 3.10 V, while it is only 2.86 V for the PVDF binder at a 5C rate. Moreover, even at a 10C rate, the PEO-b-PAN binder still delivers extraordinary discharge capacities of 101 mAh g −1, significantly higher than that of the PVDF binder (32 mAh g −1 ). Overall, this ionic conducting and surface active binder exhibits good electrochemical properties and excellent high rate performance.